2019
DOI: 10.3390/nu11020389
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lower Intake of Minerals and Depressive Symptoms among Elderly Japanese Women but Not Men: Findings from Shika Study

Abstract: The aim of this cross-sectional study was to examine the relationship of mineral intake, including sodium, potassium, calcium, magnesium, phosphorus, iron, zinc, copper and manganese, with depressive symptoms in both genders in the Japanese elderly population. A total of 1423 participants who were older than 65 years old were recruited in this study. Mineral intake was analyzed using a validated and brief self-administered diet history questionnaire. Depressive symptoms were assessed with a short version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 59 publications
(67 reference statements)
8
34
1
Order By: Relevance
“…Thi Thu Nguyen et al (2019) stated that a strong statistically inverse relation between depressive symptoms and serum Ca level (18). Also, the study by Miki et al2015 suggested that a higher dietary intake of Ca was associated with a lower prevalence of depressive symptoms (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thi Thu Nguyen et al (2019) stated that a strong statistically inverse relation between depressive symptoms and serum Ca level (18). Also, the study by Miki et al2015 suggested that a higher dietary intake of Ca was associated with a lower prevalence of depressive symptoms (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies tackled the association of depression with CLD (15,16) while other studies search the relationship between trace elements and depression (17,18) but data about the association between depression in CLD and macroelements and TEs are limited. So the aim of our study is to detect the relationship between TEs, macro-minerals, and depression among older patients with CLD.…”
Section: Introductionmentioning
confidence: 99%
“…Hostile male medical students seem to prefer salt (127) , and low dietary Na contributes to depression in Japanese men and marginally in American women, who may self-medicate with salt to improve their mood (39,101) . Other research has failed to relate the two or indicated cultural and dietary dependence, and yet other studies suggested salt may increase anxiety and even panic (127)(128)(129)(130)(131)(132) .…”
Section: Conditioning Salt Preference Through Exertion Mood Health mentioning
confidence: 99%
“…In addition, the hormone also inhibits the 5-hydroxytryptamine 3 (5-HT3) receptor, which is responsible for the serotonin uptake in the synaptic cleft, thereby reducing the stimulation of the target cell [12]. Antidepressants from the selective serotonin reuptake inhibitor (SSRIs) group have a similar effect.When analyzing the pathophysiology of depression symptoms, we should note the changes in concentrations of bioelements, as they may underlie the mechanisms leading to emotional disorders as well as clinical depression [13][14][15][16]. In suffering patients, magnesium supplementation has been used, as it affects several biochemical pathways in the brain responsible for apathy [17].…”
mentioning
confidence: 99%
“…When analyzing the pathophysiology of depression symptoms, we should note the changes in concentrations of bioelements, as they may underlie the mechanisms leading to emotional disorders as well as clinical depression [13][14][15][16]. In suffering patients, magnesium supplementation has been used, as it affects several biochemical pathways in the brain responsible for apathy [17].…”
mentioning
confidence: 99%